(untitled) (2011)
Significant progress has been made during recent yearsin applying information technologiesto water resource management from a multidisciplinary field called hydroinformatics; this can change the focus of environmental impact assessment and decision-making according to available environmental resources. This article presents an image retrieval system which uses the Universidad de la Amazonia's (Colombia)Aquatic Ecosystem Quality and Preservation Research Group's (CAPREA) digital image collection. Automaticpicture classification (having attributes relative to water colour, edges and flow type) is proposed which has beenbased onDinnertein's classification, adapted by the Universidad Nacional de Colombia'sHydrology and Meteorology Institute and Environment Studies in 2001.